A Molecular Framework for the Control of Adventitious Rooting by TIR1/AFB2-Aux/IAA-Dependent Auxin Signaling in Arabidopsis - Lakehal, Abdellah; Chaabouni, Salma; Cavel, Emilie; Le Hir, Rozenn; Ranjan, Alok; Raneshan, Zahra; Novák, Ondřej; Păcurar, Daniel I; Perrone, Irene; Jobert, François; Gutierrez, Laurent; Bakò, Laszlo; et al. (Molecular plant, 2019)
In Arabidopsis thaliana, canonical auxin-dependent gene regulation is mediated by 23 transcription factors from the AUXIN RESPONSE FACTOR (ARF) family that interact with auxin/indole acetic acid repressors (Aux/IAAs), which themselves form co-receptor complexes with one of six TRANSPORT INHIBITOR1/AUXIN-SIGNALLING F-BOX (TIR1/AFB) proteins. Different combinations of co-receptors drive specific sensing outputs, allowing auxin to control a myriad of processes. ARF6 and ARF8 are positive regulators of adventitious root initiation upstream of jasmonate, but the exact auxin co-receptor complexes controlling the transcriptional activity of these proteins has remained unknown. Here, using loss-of-function mutants we show that three Aux/IAA genes, IAA6, IAA9, and IAA17, act additively in the control of adventitious root (AR) initiation. These three IAA proteins interact with ARF6 and/or ARF8 and likely repress their activity in AR development. We show that TIR1 and AFB2 are positive regulators of AR formation and TIR1 plays a dual role in the control of jasmonic acid (JA) biosynthesis and conjugation, as several JA biosynthesis genes are up-regulated in the tir1-1 mutant. These results lead us to propose that in the presence of auxin, TIR1 and AFB2 form specific sensing complexes with IAA6, IAA9, and/or IAA17 to modulate JA homeostasis and control AR initiation.
Keywords: Arabidopsis Proteins; stabilita proteinů; AuxIAA; Protein Stability; Indoleacetic Acids; F-Box Proteins; F-box proteiny; jasmonate; adventitious roots; signální transdukce; hypokotyl; Signal Transduction; proteiny huseníčku; Hypocotyl; Plant Roots; Gene Expression Regulation, Plant; kyseliny indoloctové; regulace genové exprese u rostlin; receptory buněčného povrchu; TIR1/AFB; Receptors, Cell Surface; Arabidopsis; kořeny rostlin